SUPERVISI PEMBELAJARAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU IPS DI SMP NEGERI 2 KOTA TERNATE - Rustam Hasyim; Mukhtar Yusup (EDUKASI, 2017)
This research to describes the supervision by Supervisor. In education needs supervision because it is the part of point effort to increase the learning achievement and quality of school. The effort to improving competence of teacher and head master its can done by given helping professional like as implementation, consultation and guidance, and also the activities that related with the improvement of competence quality. Every supervisor demand to have the base of certain capability than other in educational.  The  base  capability  called  competence.  Competence  is  knowledge,  skill/know-how, ability or capacity to get to someone that becomes part of its situation until supervisor has capability to  do  to  cognitive  agent,  affective  and  certain  psychomotor  in  optimal.  The  conceptual  of  this research as follow: (1).Supervision management, (2). Supervision’s effectiveness by supervisor, (3).Supervision management to increase the education quality of teacher. This research used qualitative  method  and  descriptive  approach.  Technique  to  determining  the  data  is  purposive samling, its focus to the key of informant is actors in implementation and as an actor in carrying out of the location. Getting the data, primer data although secondary data its based on the observation, documentation and focus interview (in-depth-interview) that used the guidelines of interview not structure. The next getting data is verification and analysis with the theorist interpretation. The findings of this research are some points related with the obstacles that appear in supervision management by supervisor in Department of National education area of Ternate city. (1). less care from government to increase the professionalism of supervisor, (2). less facility of transportation for supervisor, (3). Not yet the different from other’s room for supervisor, (4). less guidance supervision book of supervisor, (5). Less comprehension about supervision concept of supervisor, (6). The teacher’s supervision don’t prepare the learning set of equipment when get the supervision, (7). Almost the teacher came late in the first class when the supervisor to do to supervision, (8). Used time is not affective by teacher when supervisor get the supervision, (9). Management class is not effective by teacher when supervisor get supervision. Key Word: Supervision Management, teachers’ competence